Pelaksanaan kurikulum 2013 di Sekolah Menengah Kejuruan Negeri 3 (SMKN 3) Kota Banda Aceh - Fadhilah, Razali (2018)
This study is based on the issue of Curriculum 2013 which is one of the curriculum changes. Nevertheless, there are weaknesses in the curriculum that need to be deliberated. Besides, the ability of teachers is also restricted in the effective implementation of the curriculum. Therefore, the implementation of the curriculum requires teachers' understanding. Teachers who do not have the understanding will encounter difficulties in implementing this curriculum. Hence, Curriculum 2013 that is recognized as co-owned is a curriculum of imitation from other schools that have implemented it. The objective of this study is to assess the level of understanding of teachers in implementing Curriculum 2013 that is called K13 which involves teachers’ understanding in formulating lesson plans (RPP), learning models, learning media and learning module. A qualitative study based on a case study approach was used as the design of the present study. Study participants were teachers at the vocational school (SMKN) 3 in Banda Aceh. By using a qualitative method, the researcher was able to identify the level of understanding of the teachers in SMK 3 Banda Aceh in implementing Curriculum 2013. Purposive sampling consisting of principals and teachers of SMK 3 Banda Aceh was used. The researcher collected data through interviews, participant observation, and analysis of documents which is done through content analysis. The study found that teachers do not have a comprehensive understanding of the Curriculum 2013 that hinders them from implementing it. The findings showed that teachers had difficulty in designing lesson plans, using the model, using the medium of learning and developing learning modules. Therefore, in order to increase understanding of the implementation of Curriculum 2013, the support in implementing Curriculum 2013 is a decisive factor contributing to the successful implementation of Curriculum 2013. In constructing the lesson plans, teachers can pay attention to the principles in building the RPP, using a variety of learning models, learning media and the design of the module. In addition, the school principal is expected to have a good rapport with the various education departments be it in the city and central level so that opportunities are given to render training for all the teachers in SMK 3 Banda Aceh